Layer-by-Layer Assembled Multilayer Films for Transcutaneous Drug and Vaccine Delivery - Su, Xingfang (2009)
We describe protein- and oligonucleotide-loaded layer-by-layer (LbL)-assembled multiplayer films incorporating a hydrolytically degradable polymer for transcutaneous drug or vaccine delivery. Films were constructed based on electrostatic interactions between a cationic poly(β-amino ester) (denoted Poly-1) with a model protein antigen, ovalbumin (ova), and/or immunostimulatory CpG (Cytosine–phosphate diester—Guanine rich) DNA oligonucleotide adjuvant molecules. Linear growth of nanoscale Poly-1/ova bilayers was observed. Dried ova protein-loaded films rapidly deconstructed when rehydrated in saline solutions, releasing ova as non-aggregated/non-degraded protein, suggesting that the structure of biomolecules integrated into these multilayer films are preserved during release. Using confocal fluorescence microscopy and an in vivo murine ear skin model, we demonstrated delivery of ova from LbL films into barrier-disrupted skin, uptake of the protein by skin-resident antigen-presenting cells (Langerhans cells), and transport of the antigen to the skin-draining lymph nodes. Dual incorporation of ova and CpG oligonucleotides into the nanolayers of LbL films enabled dual release of the antigen and adjuvant with distinct kinetics for each component; ova was rapidly released while CpG was released in a relatively sustained manner. Applied as skin patches, these films delivered ova and CpG to Langerhans Cells in the skin. To our knowledge, this is the first demonstration of LbL films applied for the delivery of biomolecules into skin. This approach provides a new route for storage of vaccines and other immunotherapeutics in a solid-state thin film for subsequent delivery into the immunologically-rich milieu of the skin.